Graded Epidural Anesthesia with Real-Time Hemodynamic Monitoring for Cesarean Delivery in Severe Mitral Stenosis: A Case Report - Kurniady, Stephanie; EM, Tjahya Ariyasa; Putra Pradana, Adinda (Udayana University and Indonesian Society of Anesthesiologists (PERDATIN), 2025)
This case report highlights the successful management of a high-risk obstetric patient with severe rheumatic mitral stenosis (MS) and acute decompensated heart failure (ADHF) using graded epidural anesthesia guided by real-time hemodynamic monitoring. A 34-year-old woman, in her second pregnancy following a previous abortion, presented at 34 weeks and 5 days of gestation with progressive dyspnea and orthopnea. Echocardiography confirmed severe MS accompanied by pulmonary hypertension and preserved left ventricular systolic function. After multidisciplinary optimization, an elective cesarean delivery was performed under graded epidural anesthesia with incremental dosing of lidocaine and ropivacaine. Beat-to-beat cardiac output monitoring using the MostCare™ PRAM (Pressure Recording Analytical Method) system guided vasopressor titration with phenylephrine, maintaining hemodynamic stability. The patient remained hemodynamically stable throughout the intraoperative and postoperative periods, with no pulmonary edema or arrhythmias, and was discharged on postoperative day four. This case demonstrates that graded epidural anesthesia, when combined with advanced hemodynamic monitoring and collaborative care, represents a safe and effective alternative to general anesthesia in parturients with severe valvular heart disease.